INTERNALISASI NILAI-NILAI MODERASI BERAGAMA MELALUI PEMBELAJARAN AKIDAH AKHLAK (STUDI DI MADRASAH ALIYAH HIDAYATUL ISLAMIYAH TUBAN) - Moh. Mundzir Mundzir; Sholikah Sholikah; Rahma Eva Rini (Program Studi Manajemen Dakwah, Fakultas Dakwah, Institut Agama Islam Nahdlatul Ulama Tuban, 2023)
This article focuses on the problem (1) What are the values of religious moderation in the learning of class X moral creed at MA Hidayatul Islamiyah Sumberagung? (2) How is the process of internalising the values of religious moderation in learning class X moral creed at MA Hidayatul Islamiyah Sumberagung? (3) How is the impact of internalising the values of religious moderation in learning class X moral creed at MA Hidayatul Islamiyah Sumberagung. Based on the formulation of the problem, this study aims to (1) Describe the values of religious moderation in learning the morals of class X at MA Hidyatul Islamiyah Sumberagung (2) Describe the process of internalising the values of religious moderation in learning the morals of class X at MA Hidayatul Islamiyah Sumberagung (3) Describe the impact of internalising the values of religious moderation class X at MA Hidayatul Islamiyah Sumberagung. The research method used is qualitative research combined with descriptive and uses triangulation to test the validity of the data. Data collection techniques were carried out through observation, interviews and documentation. Data analysis is done through data collection, data reduction, data presentation, and conclusion drawing. Based on the results of data collection, it shows that the internalisation of religious moderation values in class X moral teaching applies contextual methods through the process of value transformation, value transactions, and value internalisation. The goal is to internalise the values of tolerance, fairness, deliberation, love for the country, and exemplary to students.